PENGELOLAAN TENAGA PENDIDIK DAN KEPENDIDIKAN DALAM PONDOK PESANTREN - Bashirotul Hidayah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2022)
Pesantren is one of the educational realities that has been entrenched among some nations, especially among the majority of Muslims who are the majority group in Indonesia. Pesantren is one type of traditional Indonesian Islamic education to explore Islamic religious knowledge and practice it as a daily life guide or called Tafaqquh Fiddin. Educators themselves are professionals who are tasked with planning and implementing the learning process, assessing learning outcomes, conducting guidance and training, as well as conducting research and community service, especially for educators at universities. The management of teaching staff at Madrasah Hidayatul Muhibbin is to be qualified in religious matters, so that this institution can select and sort out educators in accordance with the Madrasa's vision and mission through the recruitment of educators or Mustahiq/Mudarris. Then for educators and education staff if they experience difficulties in teaching and learning activities (KBM) both in science or classroom conditioning, Madrasas have prepared a forum as a place for consultation regarding the problems experienced.